Implementasi Kewirausahaan dan Koperasi di Sekolah Pada MI , Roudlotul Jannah Bilingual Prambon Kab. Sidoarjo - Setiono, Hari; Khanida, Marisha; Ilmiddaviq, Muhammad Bahril (ABDIMAS NUSANTARA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Community Service Activities to implement one of the Higher Education Laws. In addition, by serving the community, the existence of universities is expected to make a major contribution to the development and application of science to the community. Especially the teacher of MI students Roudlotul Jannah Bilingual Prambon Sidoarjo. The method used in this community service is exposure, namely oral and investigative documentation, namely learning that emphasizes analytical and critical thinking processes related to knowledge, business knowledge and descriptions that are directly related to the type of business, innovative and creative ideas in startups, such as an effort made by collecting used goods. Usefulness can be converted into bags, souvenirs that can be sold using easily available tools and materials. The results of community service produced increase the knowledge of teachers and students of MI Roudlotul Jannah Bilingual about entrepreneurship and they have the ability to apply the knowledge and skills acquired in this community service and should be able to provide new enthusiasm for entrepreneurship. Keywords Entrepreneurship, Cooperatives and Schools